THE ROLE OF IRRATIONAL BELIEFS AND PERCEIVED STRESS IN THE DEVELOPMENT OF DYSFUNCTIONAL ATTITUDES AMONG STUDENTS - Simona A. PASCAL; Alina C. CHIVU (Revista de Pedagogie, 2022)
The literature raises concerns in terms of the psychological functioning of the students. Their well-being can be impaired by some problems they may face, like academic, personal, financial, or social ones. Cognitive theories support the fact that at the origin of the psycho-emotional consequences lies a dysfunctional thinking pattern. It can determine how people perceive events or their attitudes regarding the situations they experience. All these aspects play an important role in mental health. Thus, the first objective of the present study was to identify possible associations between dysfunctional attitudes, irrational beliefs, and perceived stress among students. The second objective was to test whether the relationship between irrational beliefs and dysfunctional attitudes is explained by perceived stress, through a mediation model. In this research, 148 students filled in three psychological scales that measure the following constructs: dysfunctional attitudes, irrational beliefs, and perceived stress. In general, the results emphasized negative and weak associations between attitudes and cognitions (r = -.265, p = .001) and perceived stress and attitudes (r = -.167, p = .043), but a positive relationship between cognition and perceived stress (r = .312, p < .001). Also, the mediation analysis showed that there are misgivings that perceived stress does explain the relationship between irrational cognitions and dysfunctional attitudes. These preliminary findings could be an initial step in the educational environment to improve the beliefs and attitudes assessment among students by targeting them as important elements.